Characteristics of Foreign Subsidiaries in Industry Clusters - Birkinshaw, Julian; Hood, Neil (Journal of International Business Studies, 2000)
This paper examines the characteristics of foreign-owned subsidiaries in export-intensive “leading-edge industry clusters” as defined by Porter [1990]. Using a sample of 229 subsidiaries from three countries, we show that subsidiaries in such clusters are more embedded, more autonomous, and more internationally-oriented than subsidiaries in other industry sectors. We also show that there are significant differences in the roles of foreign-owned subsidiaries from one leading-edge cluster to the next, that are associated with the dynamism of the cluster and the overall level of foreign ownership. The results indicate (1) that typologies of subsidiary roles should give increased consideration to environmental factors, and (2) that thinking on industry clusters, instead of treating them identically, should recognize that they have heterogeneous characteristics.